Association study of polymorphism in the serotonin transporter gene promoter, methylation profiles, and expression in patients with major depressive disorder. (23rd March 2016) - Iga, Jun‐ichi; Watanabe, Shin‐ya; Numata, Shusuke; Umehara, Hidehiro; Nishi, Akira; Kinoshita, Makoto; Inoshita, Masatoshi; Shimodera, Shinji; Fujita, Hirokazu; Ohmori, Tetsuro
Abstract : The serotonin transporter (5HTT) may be associated with the pathogenesis of major depressive disorder (MDD). The 5HTT‐linked polymorphic region (5HTTLPR) genotype may determine how levels of 5HTT mRNA are influenced by promoter methylation. We examined the association of 5HTT gene methylation, which influences gene expression, and the 5HTTLPR genotype before antidepressant treatment and expression before and after treatment. The aims of this study were (1) to investigate the association between 5HTT methylation or expression in leukocytes and depression and (2) to investigate a possible effect of 5HTT methylation, expression, and genotype on clinical symptoms in MDD. The 5HTTLPR genotype was significantly associated with mean methylation levels in patients only (patients: r = 0.40, p = 0.035, controls: p = 0.96). The mean methylation level was significantly increased in patients compared with controls (patients: 5.30 ± 0.24, controls: 4.70 ± 0.19, unpaired t ‐test, p = 0.04). 5HTT expression using real‐time PCR and Taqman probes was increased in unmedicated patients compared with controls and then decreased 8 weeks after antidepressant treatment. The mean 5HTT expression level was not associated with the 5HTTLPR genotype in patients or controls. Increased depressive symptoms were related to decreased levels of methylation. Copyright © 2016 John Wiley & Sons, Ltd.